The Impact of Organizational Commitment and Compensation on Police Job Satisfaction at the North Sulawesi Regional Police - Syafruddin Syafruddin; Donald Happy Ginting (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2026)
Job satisfaction is an important factor in improving organisational performance and effectiveness, especially in public sector institutions such as the Indonesian National Police. Police officers' job satisfaction is influenced by various organisational factors, including organisational commitment and compensation provided by the institution. Organisational commitment reflects the level of attachment of members to the organisation, while compensation is a form of reward for work contributions that can influence the attitudes and work motivation of members. This research was designed to investigate the relational dynamics linking organisational commitment with job satisfaction and to assess the contributory role of compensation in shaping the job satisfaction of Indonesian National Police (Polri) officers operating within the jurisdiction of the North Sulawesi Regional Police. Adopting a quantitative methodological orientation, the study utilised multiple linear regression modelling facilitated by SPSS software. Primary data were collected from 352 police personnel using a Likert-scale survey with random sampling. The analytical sequence incorporated instrument validity and reliability diagnostics, followed by hypothesis verification using t-test and F-test statistics. The analytical outcomes reveal that organisational commitment manifests a positive relational tendency with job satisfaction among Polri members. Further, compensation emerges as a significant positive determinant of job satisfaction. These observations suggest that heightened organisational commitment together with a more favourable compensation arrangement correspond with increased levels of job satisfaction among police officers. Accordingly, the study highlights the strategic relevance of commitment cultivation and compensation management in reinforcing personnel welfare, institutional loyalty, and professional performance within the policing apparatus.